2019
DOI: 10.1371/journal.pone.0219146
|View full text |Cite
|
Sign up to set email alerts
|

Response of peripheral arterial pulse wave velocity to acute exercise in patients after recent myocardial infarction and healthy controls

Abstract: Background Many studies found increased central arterial stiffness and poor endothelial function in patients with coronary artery disease (CAD). Acute exercise has been shown to decrease peripheral pulse wave velocity (pPWV) in young healthy volunteers. We hypothesized the response to acute exercise to be diminished in CAD patients compared to healthy young (HY) and age-matched (HAM) controls. Methods In 21 patients after recent myocardial infarction (CAD), 11 HAM and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…This effect could be mediated by the alteration of vascular muscle with exercise, possibly induced by components such as endothelium-derived hyperpolarizing factor [ 68 ]. The peripheral PWv after exercise shows vessel dilation due to increased shear stress, decreased vessel wall thickness, and reduced vasomotor tone [ 69 ]. In fact, our findings in the peripheral PWv could be bigger than the results of the present study are showing because the data of the mixed central and peripheral PWv have been considered as data of the peripheral PWv and, as a consequence, in mixed (central and peripheral) PWv, the central PWv could have blunted the effect of the peripheral PWv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect could be mediated by the alteration of vascular muscle with exercise, possibly induced by components such as endothelium-derived hyperpolarizing factor [ 68 ]. The peripheral PWv after exercise shows vessel dilation due to increased shear stress, decreased vessel wall thickness, and reduced vasomotor tone [ 69 ]. In fact, our findings in the peripheral PWv could be bigger than the results of the present study are showing because the data of the mixed central and peripheral PWv have been considered as data of the peripheral PWv and, as a consequence, in mixed (central and peripheral) PWv, the central PWv could have blunted the effect of the peripheral PWv.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure and PWv are closely related, so much so that it is still debated whether the former represents a cause or a consequence of the latter [ 70 ]. During exercise there is an increase in blood pressure, probably due to the action of the sympathetic nervous system [ 69 ]. Immediately after exercise, there is hypotension in the systolic and diastolic blood pressure that lasts up to two hours [ 69 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A priori power analysis with G*Power (version 3.1.9.7, Heinrich Heine University, Düsseldorf, Germany) was performed, using a predefined power of 0.80, an effect size of 0.94 and an alpha level of 0.05 [ 20 ]. According to the parameters, this led to a required sample size of at least 15 participants in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Because exercise training consists of repeated bouts of acute endurance exercise, it is necessary to understand the effect of acute endurance exercise on venous vascular properties. It has been reported that the decrease in arterial stiffness after acute endurance exercise seems to be caused partly by enhanced endothelial function (Saz‐Lara et al, 2021 ; Trachsel et al, 2019 ). In addition, acute endurance exercise elicits the production of endothelial nitric oxide (NO) by increasing blood flow and shear stress (Mochizuki et al, 1999 ; Shen et al, 1995 ), and this enhanced NO synthesis modulates arterial stiffness (Wilkinson et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%